Preparation of cardan joint by selective laser sintering and properties of polyamide-12 and portland cement powder mixture. - Saleh Ahmed Aldahash (PLoS ONE)
A homogeneous mixture of polyamide-12 (PA-12) and Portland cement (PC) powder material was prepared using the Sinterit sifter. Many techniques were used to detect morphological and functional properties. The scanning electron microscope confirms the proper mixing of both components. Thermal testing indicates that at 453.15 K, the change in molecular weight occurred more rapidly. The results of differential scanning calorimetry confirm that as the molecular weight increases, the glass transition temperature and melting temperature increase while the crystallization temperature of the material decreases. According to the results, a mixture of PA-12 and PC powder exhibits excellent mechanical properties, making it suitable for various applications. Thermally, mechanically, and chemically, they are often the best choice in the most demanding applications that require both high mechanical strength and durability at high temperatures. Due to this, polyamide powders and cement mixtures with narrow particle sizes show promise for additive manufacturing and selective laser sintering. This study focuses on developing a new mixture material by combining cement additives with PA-12 to reduce costs and enhance the mechanical properties of sintered specimens (cardan joints). The blended material will cost less than pure PA-12 because cement is significantly cheaper than PA-12.